The complementarity between trust and contract enforcement - Björn Bartling; Ernst Fehr; David Huffman; Nick Netzer (University of Zurich, Department of Economics, 2021)
Under weak contract enforcement the trading parties' trust, defined as their belief in other's trustworthiness, appears important for realizing gains from trade. In contrast, under strong contract enforcement beliefs about other's trustworthiness appear less important, suggesting that trust and contract enforcement are substitutes. Here we show, however, that trust and contract enforcement can be complements, and identify the key mechanisms that drives this complementarity. We demonstrate that under weak contract enforcement trust has no effect on gains from trade, but when we successively improve contract enforcement, larger effects of trust emerge. Likewise, improvements in contract enforcement lead to no increases in gains from trade under low initial trust, but generate high increases in gains from trade when initial trust is high. We identify three key mechanisms: (1) heterogeneity in trustworthiness; (2) strength of contract enforcement affecting the ability to elicit reciprocal behavior from trustworthy types, and screen out untrustworthy types; (3) trust beliefs determining willingness to try such strategies.
Keywords: C91; D02; D91; E02; 330; Trust; contract enforcement; complementarity; equilibrium selection; causal effect; screening; belief distortions; institutions